Tradition vs. Transformation: Ambivalent Immigrant Identity in Gene Luen Yang’s American Born Chinese - Adhikari, Hari R. (Literary Studies, 2015)
Jin Wang, the protagonist of Gene Luen Yang’s graphic novel American Born Chinese, hates almost everybody around him simply because no one tries to understand him. Yang’s portrayal of this Asian-American youth nudges his readers to ponder on the challenges facing minority youths in their efforts to survive in an environment where people with difference feel alienated. Jin is pushed to such an extreme by the unaccommodating school atmosphere that he gradually develops self-hatred. As the tension builds up, he acts like a paranoid and becomes ready to “barter his soul” all for getting an acceptance in the white dominated community. Jin’s traumatic experiences and neurotic behaviors raise a number of questions about the life of immigrant children in the United States. How difficult is it to grow up in an alienating environment? Can parents gauge the depth of the trauma their children are going through? Are American schools safe places for children of minority cultural backgrounds? How much do stereotypes about certain cultures and nationals shape people’s attitude towards others? This paper will explore these issues focusing on the experiences of immigrant children in the novel.